Peningkatan Keterampilan Berbicara Siswa Melalui Teknik Problem Solving - Micha Felayati Silalahi; naisa naisa (Medan State University, 2021)
The main problem of this research namely, the students’ speaking skill is still poor causes them to feel embarrassed and insecure if they are asked to express their opinions. This research aims to analyze speaking skills using group guidance services with problem-solving techniques on grade IX students of SMP Negeri 2 Sarjo. The research subjects were 7 people. The questionnaire was used to collect data about speaking skills. The questionnaire was used to collect data about speaking skills. The questionnaire result data were analyzed using descriptive and inferential analysis. Hypothesis testing is carried out through statistical analysis using the Wilcoxon Sign Rank Test formula at the 95% (0,05) confidence level. The result of the descriptive analysis showed that the speaking skill of the students before participating in group guidance services with problem-solving techniques that 4 students or 57,14% are fair, 3 students or 42,86% are poor. The speaking skills of students after attending group guidance service with problem-solving techniques that 3 students or 42,86% are fair and 4 students or 57,14% are good. The inferential analysis result showed that the t-test value is 0,018 < t-table 0,05. It means that H0 is rejected. Based on the results, it can be concluded that group guidance services with problem-solving techniques is effective in improving the speaking skills of grade IX students of SMP Negeri 2 Sarjo.